ANALISIS DESKRIPTIF: PROFIL GABUNGAN KELOMPOK TANI (GAPOKTAN) PERKOTAAN BERPRESTASI TINGKAT PROPINSI DIY TAHUN 2016 (STUDI KASUS DI GAPOKTAN MUJA-MUJU) - Nurlaela, Siti (Jurnal Ilmu-Ilmu Pertanian, 2016)
This study focused on the exposure of the urban Gapoktan profile achievement, namely the successful management case studies Gapoktan - Muja Muju located in Muja Muju Umbulharjo District of the city of Yogyakarta. This study aimed to analyse the profile Gapoktan Muja Muju as described and shown in the research results. The quantitative data was obtained by through observation, interviews, and in-depth study of the document. Aspects of its high strength Gapoktan Muja Muju lies in the administrative neatness and tidiness is shown by the completeness of the data, activities and group dynamics, the ability to establish a network of cooperation and the achievements on the race of processed agricultural products. The medium strength aspects were on the development of venture capital (growth of 8%) per annum, marketing products and processed agricultural products. The low strength aspects were on crop production, and production infrastructure providers.